Social Representations of Mental Illness Among the Serang Regency Ciomas Community in Indonesia - Putri, Edira; Prawiro, Ferdinand (Makara Human Behavior Studies in Asia, 2018)
How mental illness is perceived by the members of a particular society will determine their treatment of those they regard as mentally ill. A primary factor which shapes the understanding of mental disorders and those who suffer from them are the social discourses that revolve around them as social objects. This study was conducted in order to understand the social representation of mental disorders among community members of Ciomas Subdistrict in Serang, Banten, and how the community as a social group views mental disorders and related physical restraints through social discourse. The dynamics of common understandings of mental disorder was investigated via the dialogical approach of Social Representation Theory, specifically by using the concept of themata. Themata is an underlying deep structure of meanings that provides a basis to the establishment of a social representation. Through a qualitative focused group discussion, participants were asked to convey and describe their understanding of mental disorders. Three underlying antinomies were identified, where each contributes to shaping a common understanding of mental disorders, namely [1] supernatural–natural, [2] inhuman–human, and [3] nature–nurture. These antinomies not only explain the underlying understanding of mental disorders but also serve as a ground in understanding various treatments for people with mental disorders in the community, including physical restraints.